1995
DOI: 10.1002/jemt.1070320604
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Sertoli cell microtubules, microtubule‐dependent motors, and the Golgi apparatus before and after tight junction formation in developing rat testis

Abstract: Sertoli cells are polarized epithelial cells of the seminiferous epithelium which provide structural and physiological support for differentiating germ cells. They establish different basal and adluminal environments for the selective nurturing of pre- and post-meiotic germ cells within the seminiferous epithelium, segregated by the Sertoli-Sertoli cell tight junctional complex, the blood-testis barrier. Tight junction formation between epithelial cells in vitro is a critical polarizing event associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Microtubules are components of the cytoskeleton, it is the fundamental unit of the spindle that is required for mitotic and meiotic cell division (Helmke, Heald, & Wilbur, ). Sertoli cell microtubule networks are likely to be required for the transport of cargoes through the extensive cytoplasm that in turn are needed for normal cellular function and the ability to support the germ cell development (Neely, ; Redenbach & Boekelheide, ). During sperm release phase, the microtubules around the nucleus and in the cytoplasm have a role in maintaining Sertoli cell structural integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules are components of the cytoskeleton, it is the fundamental unit of the spindle that is required for mitotic and meiotic cell division (Helmke, Heald, & Wilbur, ). Sertoli cell microtubule networks are likely to be required for the transport of cargoes through the extensive cytoplasm that in turn are needed for normal cellular function and the ability to support the germ cell development (Neely, ; Redenbach & Boekelheide, ). During sperm release phase, the microtubules around the nucleus and in the cytoplasm have a role in maintaining Sertoli cell structural integrity.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the concept that these MT-specific motor proteins and MT-based tracks are crucial to support these cellular events (12,22,65). Studies performed almost two decades ago have reported the presence of MT-based motor proteins dynein and kinesin II (Note: dynein and kinesin are minus-end-and plus-end-directed MT motor proteins, respectively) in the rodent testis, closely associated with the plus end (i.e., fast-growing end) of MTs at the Sertoli cell ES (31,60,71). Interestingly, the plus-end MTs are predominantly found near the basement membrane of the tubules but are also localized along MTs that stretch across the seminiferous epithelium (85,86,90).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that actin microfilament bundles are intimately involved with tight junction complexes between neighboring Sertoli cells (Amlani and Vogl, 1988;Boekelheide, et al, 1989;Vogl, 1989). The assembly of microfilament networks closely parallels the formation of tight junction complexes of the blood-testis barrier (Redenbach et al, 1995). Actin filament bundles occur adjacent to junctional networks and are seen to form a belt that circumscribes the base of each Sertoli cell (Vogl and Soucy, 1985;Vogl, 1989) and to undergo organizational changes during spermatogenesis (Vogl and Soucy, 1985;Amlani and Vogl, 1988).…”
Section: Discussionmentioning
confidence: 99%